"Everyone Saw Me Differently Like It Was My Fault or I Wanted It": Acquaintance Stalking Victim Experiences of Sexual Assault, Sexual Harassment, and Sexual Autonomy. Issue 13 (July 2023) - Logan, TK; Landhuis, Jennifer
Although the stalking research literature has grown over time, there is more limited research focused on acquaintance stalking victim experiences and harms. The current study used online surveys with women stalked by acquaintances who had ( n = 193), and who had not ( n = 144), been sexually assaulted by the stalker to examine differences in stalking course of conduct (including jealousy and control, sexual harassment) and victim harms (resource losses, social identity perceptions, sexual autonomy, sexual difficulties, and safety efficacy). Results found that many of the acquaintance stalking victims in the current study experienced all three types of sexual harassment (verbal harassment, unwanted sexual advances, sexual coercion) and had negative social identity perceptions (e.g., how they felt about themselves, how they felt about their ability to be a good partner). More women who were sexually assaulted, compared to those who were not, experienced threats, jealous and controlling behavior, severe physical violence, stalking-related fear, sexual harassment, negative social identity perceptions, and lower sexual autonomy. Multivariate analysis found that sexual assault, more unwanted sexual attention, increased sexual coercion, lower safety efficacy, and more negative social identity perceptions were associated with sexual difficulties while sexual assault, higher safety efficacy, fewer resource losses, and fewer negative social identity perceptions were associated with increased sexual autonomy. Sexual assault, verbal sexual harassment, and resource losses were associated with more negative social identity perceptions. Understanding the full scope of stalking victimization and the negative impacts can inform the recovery journey and safety planning interventions.